BALAI PELATIHAN PERTANIAN PADI KUBU RAYA - Andari, Amelia Gresia; Affrilyno, Affrilyno; Muazir, Syaiful (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
The agricultural sector plays an important role in economic activities in Indonesia. Kubu Raya Regency is an agricultural center area with quite large production output, a rice field area of 79,000 ha, and 1,850 farmer groups with a total of 167 farmer group organizations. Kubu Raya Regency already has a Rice Agriculture Training Center, but the facilities and space are inadequate, so development needs to be carried out to meet the needs and comfort of its users. The rice farming training center is a place to learn, practice, and practice in the field of rice farming. The aim of this study is to design a rice agriculture training center by adjusting the facility standards and user comfort of the building used for training, management, and visitor activities. The design method used in this design is the five-step design process method in the book